Metabolic syndrome, anxiety, depression and suicidal tendencies in post-traumatic stress disorder and schizophrenic patients - Maslov, Boris (Array, 2009)
Summary: Persons with schizophrenia and post-traumatic stress disorder (PTSD) tend to have higher psychiatric and somatic morbidity. They typically have higher rates of substances abuse (including smoking), more prevalent obesity, diabetes mellitus, and cardiovascular disease (CVD). This is especially well seen in case of the metabolic syndrome, with a number of published studies on psychiatric patients in the last few years. This study investigated the associations between metabolic syndrome, anxiety, depression and suicidal tendency in schizophrenic and combat-related PTSD patients controlled by healthy controls. Higher rates of anxiety, depression and recent life changes scores in participants with metabolic syndrome were recorded compared to those without metabolic syndrome. Suicidal tendencies were equally present in both groups